2020
DOI: 10.3389/fnins.2020.00651
|View full text |Cite
|
Sign up to set email alerts
|

KTN1 Variants Underlying Putamen Gray Matter Volumes and Parkinson’s Disease

Abstract: Background: Selective loss of dopaminergic neurons and diminished putamen gray matter volume (GMV) represents a central feature of Parkinson's disease (PD). Recent studies have reported specific effects of kinectin 1 gene (KTN1) variants on the putamen GMV. Objective: To examine the relationship of KTN1 variants, KTN1 mRNA expression in the putamen and substantia nigra pars compacta (SNc), putamen GMV, and PD. Methods: We examined the associations between PD and a total of 1847 imputed KTN1 single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…However, in females, the rs945270-ADHD association was not significant, even after adjusting for GMVs. Furthermore, this allele also significantly increased putamen GMV only in males, confirming previous findings [ 15 , 17 , 18 ]. The regulatory effect of the major allele C of rs945270 on GMVs was not influenced by ADHD symptom scores.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in females, the rs945270-ADHD association was not significant, even after adjusting for GMVs. Furthermore, this allele also significantly increased putamen GMV only in males, confirming previous findings [ 15 , 17 , 18 ]. The regulatory effect of the major allele C of rs945270 on GMVs was not influenced by ADHD symptom scores.…”
Section: Discussionsupporting
confidence: 91%
“…A previous genome-wide association study (GWAS) reported that the major allele C of rs945270 at 3’ flanking to the kinectin 1 gene ( KTN1 ) showed the most significant positive effect on putamen GMV ( p = 1.1 × 10 −33 ) [ 15 ], a finding confirmed by follow-up meta GWAS ( p = 1.0 × 10 −43 ) [ 16 ] and candidate gene association studies (5.0 × 10 −51 ≤ p ≤ 1.3 × 10 −5 ) [ 17 , 18 ]. This allele had also a significant positive effect on the pallium GMV ( p = 3.0 × 10 −7 ) [ 15 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In humans, KTN1 gene variants are strongly associated with KTN1 gene expression in the putamen and the volume of the putamen 113 , a region of the forebrain belonging to the basal ganglion that influences motor behaviours including motor planning and execution, motor preparation, amplitudes of movement and sequences of movement [113][114][115][116][117][118][119][120] . Here, the KTN1 G-allele was <1% in Thoroughbreds but had an average frequency of 0.22 in the other racing breeds, was 0.34 in the ancestral breeds and 0.21 in the sport horse breeds.…”
Section: Genomic Signals Of Selection Among Racing Breedsmentioning
confidence: 99%
“…Recently, Mao and colleagues reported nominal associations between common intergenic variants downstream and upstream of the KTN1 gene and PD risk, as well as an increased KTN1 mRNA expression in the putamen and SNpc, which resulted in a compensatory increase in the gray matter volumes (GMV) of these two brain regions in PD patients, suggesting that KTN1 may play a functional role in the development of PD 6 . KTN1 encodes the integral membrane protein kinectin 1, a receptor that is involved in organelle transport within the cell by allowing vesicle binding to kinesin 7 .…”
Section: Introductionmentioning
confidence: 99%